Protein-mediated fluorescence resonance energy transfer (P-FRET) probe: fabrication and hydroxyl radical detection - Yu, Xiaokan (2023)
Fluorescent probes based on fluorescence resonance energy transfer (FRET) are highly promising for diverse bioapplications. The key to constructing FRET probes is to confine the donor and acceptor within a sufficiently close distance. However, the commonly used covalent linkage often requires elaborate design and complex organic synthesis, and sometimes causes changes in the fluorescence properties of the donor and acceptor. Inspired by the binding between small molecules and protein in nature, herein, we propose a protein-mediated strategy to fabricate FRET probe. In such protein-mediated FRET (P-FRET) probe, protein acts as a carrier to simultaneously confine donor and acceptor in its cavity. As a proof of concept, we use bovine serum albumin (BSA) as a model protein, coumarin derivative as a donor and hydroxyl radical (·OH)-responsive dye fluorescein as an acceptor. Through a series of investigations, including binding parameters, fluorescence properties and detection performance, we prove that the construction of P-FRET probe is simple and feasible and the detection is sensitive. Our P-FRET strategy will provide new insights for the design of FRET probes.